THE EFFECT OF BRAND IMAGE AND PRODUCT QUALITY ON CONSUMER PURCHASE DECISIONS (Case Study on the ADIDAS Brand in Siman Ponorogo Sub-district) - La Ode Sugianto; Titin Eka Ardiana; Diana Pramudya Wardhani (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This research is about